Types of agglomeration economies: Effects on business innovation - Enrique Claver-Cortés; Bartolome Marco-Lajara; Encarnacion Manresa-Marhuenda (Contemporary Economics, 2016)
A review of the literature does not provide conclusive results about the effects caused by firm agglomeration on innovation. In order to shed light on this issue, this paper draws a distinction among three kinds of agglomeration economies and empirically tests their respective impact on business innovation. The advantage that external knowledge generated through concentration can bring to each company depends on its absorptive capacity. Hence, it is posited that this dynamic capability acts as a mediator in the relationship between agglomeration and innovation. Using data from a survey conducted in 2013 by the Technological Innovation Panel (PITEC), an analysis of these ideas was performed using a sample of 2,906 high and medium-high technology companies. The results obtained indicate that several types of agglomeration economies exist and that the net effect each one of them has on innovation is different. More specifically, only urbanization economies favor innovation. Additionally, all of our findings reveal that firms increase their greater absorptive capacity in the context of agglomeration.
Keywords: O3; 330; Innovation; Agglomeration; Externalities; Absorptive Capacity